As Syllable from Sound: Evaluating Auditory Arguments - Kišiček, Gabrijela; Hinton, Martin (Informal Logic, 2024)
This paper addresses the problem of how to identify and evaluate arguments made in a nonverbal form. Such arguments may employ images, sounds, or a combination of these in a truly multimodal presentation. Here, we concentrate on those which are classified as auditory, i.e. contain at least one premise or the conclusion in sound form. We propose and test a solution whereby some elements of the Comprehensive Assessment Procedure for Natural Argumentation (CAPNA) are modified to allow for the evaluation of auditory arguments. The results of this approach are illustrated with the help of a number of authentic examples.